2013
DOI: 10.1186/2045-4015-2-29
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization of patients with schizophrenic and affective disorders in Israel in the aftermath of the structural and rehabilitation reforms

Abstract: BackgroundIn the last decade (2001–2010) the Ministry of Health implemented two major inter-related reforms: a ’structural reform’ to reduce the number of psychiatric beds and the ’Rehabilitation of the Mentally Disabled in the Community Law’, which allocated funds for a variety of residential and vocational programs in the community for these patients. The objective of the present paper was to examine the impact of the two reforms on the hospitalization of schizophrenic and affective disorder patients by trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Castle et al (1991) analyzed the evolution of the incidence of different psychotic disorders in Camberwell (London) between 1965 and 1984 and found an increase (19.9 per 100,000 persons per year in 1964-69, 24.9 in 1980-84), while in Nottingham, Kirkbride et al (2009) found that there was no overall difference between 1978 and 1999, however there was an increase of substance-induced psychotic disorders. In Taiwan, first hospital admission for people with a diagnosis of schizophrenia decreased between 1998 and 2007 (Chiang et al, 2017), and this was replicated in Israel (Levinson and Lerner, 2013). However, it is likely that these findings reflected he transition to community-based treatment, as opposed to a decline in the incidence of psychotic disorders.…”
Section: Introductionmentioning
confidence: 96%
“…Castle et al (1991) analyzed the evolution of the incidence of different psychotic disorders in Camberwell (London) between 1965 and 1984 and found an increase (19.9 per 100,000 persons per year in 1964-69, 24.9 in 1980-84), while in Nottingham, Kirkbride et al (2009) found that there was no overall difference between 1978 and 1999, however there was an increase of substance-induced psychotic disorders. In Taiwan, first hospital admission for people with a diagnosis of schizophrenia decreased between 1998 and 2007 (Chiang et al, 2017), and this was replicated in Israel (Levinson and Lerner, 2013). However, it is likely that these findings reflected he transition to community-based treatment, as opposed to a decline in the incidence of psychotic disorders.…”
Section: Introductionmentioning
confidence: 96%
“…These services were: outpatient resources with 24-h emergency access and outpatient care with high intensity, day centers and rehabilitation services, hospital and residential resources, and self-help resources. The regions included in the project had different social and cultural realities and the process of deinstitutionalization has been approached in different ways and at different times [ 24 , 25 ]. However, we have been encouraged to note that common services were available providing different types of mental health attention, which would allow continuous treatment and support the running of digital solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Desde la década pasada se ha tenido la intención de reintegrar a las PDI a la sociedad, dejando de lado la institucionalización, lo que se ha reforzado por una mejora en la calidad de los fármacos y la universalización de la seguridad social, que ha permitido la reinserción sociolaboral y familiar de las PDI; sin duda, esta tendencia está orientada al respeto del principio de beneficencia y no maleficencia, pues mejora su calidad de vida (48) .…”
Section: Principios De Beneficencia Y No Maleficencia En Los Paciente...unclassified